The effects of climatic change on glacial, proglacial and paraglacial systems at Collins Glacier, King George Island, Antarctica, from the end of the little ice age to the 21st century Los efectos de los cambios climáticos en los sistemas glaciales, proglaciales y periglaciales del glaciar Collins, isla Rey Jorge, Antártica, del final de la Pequeña Edad del Hielo al siglo XXI - Petsch, Carina; da Rosa, Kátia Kellem; Vieira, Rosemary; Braun, Matthias; Costa, Rafaela Mattos; Simões, Jefferson Cardia (Investigaciones Geográficas, 2020)
The analysis of glacial and ice-marginal systems may contribute to understanding the impact of climatic change. The aim of this study is to investigate changes in the glacial, proglacial and paraglacial system in response to the Collins glacier retreat, between the Little Ice Age (LIA) and 2070. Glacial geomorphological mapping reveals landforms that are diagnostic of a terrestrial-terminating glacier in the past. Glacial and the proglacial systems were mapped to evaluate the ice-marginal evolution. The field measurement, satellite imagery, granulometric and morphoscopic sedimentary analysis, and geomorphological data are analyzed. The Collins glacier surface topography has been surveyed by DGNSS during 11 years (1997/98-2008/09) and for glacier area estimation in 2030, 2050 and 2070 CE. The Collins glacier lost 1.4 km2 in the period LIA-2018. Under an atmospheric warming scenario, using the temperature melt index model the glacier will lose approximately 5% of its total area until 2030 (0.90 km2) 21% (3.60 km2) by 2050, and 35% (5.90 km2) by 2070 CE. Four sectors in the proglacial zone are identified: Sector 1 displays changes on the front of the glacier since the LIA, a push moraine in only one sector, presence of flutings and moraines of recession. Sector 2 showed shrinkage around 100 meters in the period LIA-2018, presenting recessional and push moraines of about 10 meters of height. Sector 3 showed 350 meters of the shrinkage since the LIA, and recessional moraines, and absence of the push moraines. Sector 4, showed 1500 meters of the shrinkage since the LIA, a push moraine of about 12 meters high. This behavior that occurs since the LIA allows validating the future scenario model. The ice-free areas could expand 1,4 km2 by the end of 2070 decade if considered since LIA. However, it should be noted that if the glacier continues to retreat, the system will be subject to hydrological and sedimentary readjustments at various stages in the future.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Glacier retreat; Landforms; Paraglacial adjustment; Proglacial system